Impact of Storage Conditions on Moisture Content and Colour Characteristics of Roasted Arabica Coffee Using Imaging Techniques - Hasanah Johari; Mahirah Jahari; Siti Khairunniza Bejo; Nur Azuan Husin; Noor Zafira Noor Hasnan; Nur Hamizah Abdul Ghani@Hashim; Danial Fatchurrahman (Jurnal Keteknikan Pertanian, 2026)
Coffee, specifically Coffea arabica, is highly valued for its quality, aroma, and flavor. Understanding the factors affecting coffee quality is essential for farmers, industry players, and consumers. One key factor is the storage conditions, including air exposure, light, moisture, and temperature. Moisture content (MC) and color are commonly used indicators of coffee quality. This study analysed MC and colour trends of dark and medium roasted Arabica ground coffee stored under various conditions (cold vs. room temperature, airtight vs. non-airtight, and opaque vs. transparent) over a 10-week period. The results showed that the MC increased under all conditions. For dark roast, the lowest MC was observed in cold, airtight, transparent storage, whereas the highest was observed in room-temperature, non-airtight, opaque storage. For medium roast, the lowest MC occurred in cold, airtight, opaque storage, and the highest occurred in room-temperature, non-airtight, transparent storage. Color analysis using RGB imaging provided reliable grayscale values consistent with visual observations, although the trends fluctuated and were not strictly increasing or decreasing. Nevertheless, the method effectively distinguished roast levels, with dark roast showing lower grayscale values than the medium roast. A relationship between MC and color was also observed, where a higher MC corresponded to higher grayscale values (slightly brighter appearance). Overall, this study highlights the impact of storage conditions on MC and color, offering insights for improving coffee storage practices to maintain quality and freshness.